2010
DOI: 10.1007/s00066-010-2151-0
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Prospective Study of Rehabilitation Therapy in the Treatment of Radiation-induced Dysphagia and Trismus

Abstract: Rehabilitation training can improve swallow function and slow down the progress of trismus in NPC patients following radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
115
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 26 publications
2
115
1
2
Order By: Relevance
“…The participants that did not undergo TC Qigong training demonstrated a dramatic decrease in interincisor distance over the 12-month study period (Table 3). Our findings concur with those of Tang et al 6 who reported that trismus progressed quickly in NPC patients if no rehabilitation was received. They found that therapeutic exercises (TMJ active ROM exercises) prevented the progression of trismus in NPC patients after radiotherapy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The participants that did not undergo TC Qigong training demonstrated a dramatic decrease in interincisor distance over the 12-month study period (Table 3). Our findings concur with those of Tang et al 6 who reported that trismus progressed quickly in NPC patients if no rehabilitation was received. They found that therapeutic exercises (TMJ active ROM exercises) prevented the progression of trismus in NPC patients after radiotherapy.…”
Section: Discussionsupporting
confidence: 93%
“…1 Currently, the primary medical management for NPC is radiotherapy, while chemotherapy and surgery (eg, nasopharyngectomy) are elective treatments. 2 Although previous research has shown that these aggressive treatment methods can successfully control tumors and thus increase overall survival rates, 1 survivors generally experience many associated side effects, such as neck muscle fibrosis, 3,4 trismus or restricted mouth opening, 5,6 and shoulder dysfunctions. 7 The disease can also directly cause chronic symptoms, such as pain and fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies 24,42,53,54 have reported that the prevention of trismus instead of its treatment is the most desirable objective since the radiation-induced trismus is of difficult to recover. Therefore, early intervention of a physiotherapist, who is inserted in the multidisciplinary team working in the care of cancer patient, becomes extremely necessary to prevent or to reduce this frequent complication, with is occasionally ignored but with significant negative impact on the quality of life of patients with H&NC.…”
Section: Discussionmentioning
confidence: 99%
“…Since the patient had no history which might induce stroke, we strongly speculate the symptom rather rendered by radiation therapy than other causes. Although some treatment of ischemic stroke and radiation-induced brain injury is similar such as rehabilitation training [6], thrombolysis and interventional therapy are not routine treatment for radiation-induced brain injury. Given early diagnosis, clinicians might use thrombolysis, vascular angioplasty or stenting to make the patient get better prognosis before the vascular completely blocked.…”
Section: Case Reportmentioning
confidence: 99%